Neutrosophy and Health Sciences: a necessary alliance - Alfredo Pardo-Fernández; Yamilé Rodríguez-Sotomayor (Revista Información Científica, 2023)
Health is the truth of life, it is a fundamental quality of the human being that is expressed in each of its four dimensions (biological, ecological, social and spiritual) and defines human nature. The knowledge to be mobilized to understand the health-disease concept in its complexity is in Neutrosophy, it must come from a dialogue and reconciliation between the life sciences, the social sciences and the behavioral sciences.